2020
DOI: 10.24093/awej/elt2.5
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Media Application in Promoting Speaking Skill of Iraqi University learners of English: A Skype-based Study

Abstract: The purpose of this study is to investigate the impact of applying social media, specifically, using Skype devices in teaching the speaking skill (Male/Female) as a supportive environment of English language teaching. Moreover, this study seeks to find whether the designed questionnaire enjoys the required validity and reliability. As a case study, the sample of the experiment consists of seventy sophomores major in English at Mustansiriya University in Iraq. The researcher randomly divided the participants in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Therefore, the significant gains of the post-test on the speaking ability test result can be interpreted that teaching activities using CLT approach through social media can greatly enhance the speaking ability of students. The finding of the study supported the findings of (Mostafavi & Vahdany, 2016), and (Wongsa, 2018) Further, the findings of this study were congruent with the study results of (Devi et al, 2020), (Hasan Dirjal & Ghabanchi, 2020), (Hussin et al, 2020), and (Shan, 2019), which stated that the incorporation of mobile technology and different types of social media in the teaching of language can greatly enhance the speaking ability of the students due to flexible nature of social media which can be used at anytime from anywhere for learning. The studies stated that the improvement of the speaking ability after learning through incorporation of mobile technology was significant.…”
Section: Students' Speaking Abilitysupporting
confidence: 91%
“…Therefore, the significant gains of the post-test on the speaking ability test result can be interpreted that teaching activities using CLT approach through social media can greatly enhance the speaking ability of students. The finding of the study supported the findings of (Mostafavi & Vahdany, 2016), and (Wongsa, 2018) Further, the findings of this study were congruent with the study results of (Devi et al, 2020), (Hasan Dirjal & Ghabanchi, 2020), (Hussin et al, 2020), and (Shan, 2019), which stated that the incorporation of mobile technology and different types of social media in the teaching of language can greatly enhance the speaking ability of the students due to flexible nature of social media which can be used at anytime from anywhere for learning. The studies stated that the improvement of the speaking ability after learning through incorporation of mobile technology was significant.…”
Section: Students' Speaking Abilitysupporting
confidence: 91%
“…A study by Mansor and Rahim (2017) also portrayed the same result. There were apparent increasing results on a post-test speaking mark rather than the pre-test, found in a study among Iraqi University English learners (Dirjal & Ghabanchi, 2020). The researchers used skype as social media to promote speaking skills.…”
Section: Social Media and Speaking Skillsmentioning
confidence: 96%
“…In the ELLs context, speaking skills are the most significant to exhibit their communication skills for various purposes (Rao, 2019). Speaking skill, among other language learning skills, is the focus of educational specialists (Dirjal & Ghabanchi, 2020). Speaking skills play a vital role in many aspects, and there is a need for English as a Foreign Language or English (EFL) as a Second Language (ESL) learners to concentrate more on them (Rao, 2019).…”
Section: Speaking Skillsmentioning
confidence: 99%
“…A study by Li (2017) reported the uses of social media by learners at a private university in Hong Kong to access additional materials, exchange the learning materials with friends, and do collaborative learning or discussion. In the field of L2 speaking specifically, recent studies on the use of social media to facilitate the learning of speaking have been carried out in various contexts, for example, Ukraine (Mykytiuk et al, 2022), Iraq (Dirjal & Ghabanchi, 2020), Bangladesh (Mitu, 2020), and Saudi Arabia (Binmahboob, 2020;Mustafa, 2018), probably suggesting the popularity of social media as well as the relevance of social media and L2 speaking these days.…”
Section: Introductionmentioning
confidence: 99%
“…The study reported that the language instructors saw YouTube as a beneficial instructional tool that could be used to teach speaking to secondary school learners. A study involving seventy Iraqi university learners by Dirjal and Ghabanchi (2020) reported that though the use of Skype applications positively influenced learners' speaking achievement, female learners were reported to score significantly higher than their male counterparts, suggesting that female learners may benefit from learning using social media more than their male counterparts. In addition, another social media, Facebook, was reported to obtain positive attitudes from 116 Ukrainian university learners (Mykytiuk et al, 2022).…”
Section: Introductionmentioning
confidence: 99%